ANALISIS ELECTRONIC WORD OF MOUTH #Gerakan1000Tumbler PROGRAM BANDUNG CLEAN ACTION - Annisa Luthfiyyah; Itca Istia Wahyuni (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
Through #Gerakan1000Tumbler Bandung Clean Action program urging the community around the town of bandung to change the habit to bring a water bottle or tumbler from home rather than buying water in the form of pack that will produce and that garbage to lead increasing where garbage in the form of plastic constituting litter inorganic difficult to be unraveled biologically.Currently there are 2.472 post on Instagram that used #Gerakan1000Tumbler. The purpose of this study is to find, understand, and able to describe electronic word of mouth #Gerakan1000Tumbler Bandung Clean Action program. The method that used in this research are qualitative descriptive, by conducting in-depth interview to main informant of the bandung clean action program, informants supporting a volunteer #Gerakan1000Tumbler and the experts electronic word of mouth. Based on the research done, we can see that electronic word of mouth #Gerakan1000tumbler Bandung Clean Action program is not good enough, from the quality of electronic word of mouth #Gerakan1000Tumbler, quantity #Gerakan1000Tumbler and expertise messaging electronic word of mouth #Gerakan1000Tumbler.